GROSS CONVERSION EFFECIENCY (GCE) OF LABEO ROHITA FED ON FORMULATED FEED - M. P. BHILAVE; S. B. NADAF; S. V. BHOSALE (The Bioscan, 2010)
The primary objective of fish production is to produce a marketable product for maximum profit. This involves a continuous effort to reduce feed cost, while trying to maintain fish health, feed efficiency and growth. In current aquaculture, commercial feeds are often formulated to contain a slightly higher level of nutrient than required by the species for maximum growth. The extra nutrients are added to feeds to insure that the requirement for maximum growth is fulfilled. The present investigation is carried out to evaluate nutritional efficiency in terms of Gross Conversion Efficiency (GCE) in freshwater fish Labeo rohita fed on different combinations of formulated feed. Earthworm species and deoiled groundnut cake was used to formulate the feed in various combinations that is from 100% earthworm formulated feed to 100% conventional feed that is deoiled groundnut cake feed. The faecal matter was collected, dried on Filtron filter paper 201 (12.5 cm) and weighted.Simulteneously the body weights are also recorded for selected time intervals. The fishes fed on formulated feed were having highest SGR and GCE values than conventional feed.